2021
DOI: 10.1186/s10194-021-01327-2
|View full text |Cite
|
Sign up to set email alerts
|

Osmophobia in primary headache patients: associated symptoms and response to preventive treatments

Abstract: Background Osmophobia, is common among primary headaches, with prevalence of migraine. The study aimed to evaluate prevalence and clinical characteristics of patients with osmophobia in a cohort of primary headache patients selected at a tertiary headache center. The second aim was to verify the possible predicting role of osmophobia in preventive treatment response in a sub cohort of migraine patients. Methods This was an observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This might support the hypothesis, that longer disease duration increases sensory sensitization and therefore, the risk of chronification. In line with this, a study in 1170 patients with primary headaches reported, that headache patients with osmophobia in at least 20% of the headache episodes showed longer headache duration and more often allodynia and higher headache intensities [13]. Another study however, did not find an association between disease duration and interictal olfactory hypersensitivity [8].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This might support the hypothesis, that longer disease duration increases sensory sensitization and therefore, the risk of chronification. In line with this, a study in 1170 patients with primary headaches reported, that headache patients with osmophobia in at least 20% of the headache episodes showed longer headache duration and more often allodynia and higher headache intensities [13]. Another study however, did not find an association between disease duration and interictal olfactory hypersensitivity [8].…”
Section: Discussionmentioning
confidence: 86%
“…A study in 1170 patients with primary headaches showed, that osmophobia is common in patients with migraine and its subtypes, but was absent in patients with episodic tension type headache and cluster headache. Headache patients with osmophobia showed longer headache duration, more severe anxiety, depression allodynia and headache intensity [13]. A questionnaire-based study focusing on olfaction in migraineurs described odor-related disturbances as common symptoms and osmophobic complaints in almost all participants [11]; a recent study however, observed osmophobia in only 30% of migraineurs [14].…”
Section: Open Accessmentioning
confidence: 99%
“…In another study, 36% of patients with MwoA had accompanying osmophobia, which was reported as a valuable and remarkable symptom in the differential diagnosis (48). Similarly, in a recent study in which 444 patients with osmophobia were compared with 726 patients without osmophobia, it was reported that osmophobia was related to a longer headache duration and intensity in a large group of patients with migraine (49). Although in previous studies, osmophobia was mostly evaluated to occur together with photophobia/phonophobia as an indicator of the cortical and subcortical hyperexcitability in response to light, olfactory, and nociceptive stimuli (a generalized hypersensitivity to environmental stimuli) in migraine (48-50), we observed that the presence of osmophobia might support the clinical diagnosis of MwoA even in patients without phonophobia/photophobia.…”
Section: Diagnostic Challenges Of Mwoa In a Patient With I/gementioning
confidence: 90%
“…Migraineurs that present with ictal osmophobia may have more painful headaches [ 118 , 119 ]. Ictal and interictal osmophobia have been associated with a longer history of migraines or high frequency of the attacks, as well as other associated symptoms, such as cranial allodynia [ 120 , 121 , 122 ], suggesting a central sensitization process [ 123 ]. Vomiting can also be more common in the presence of osmophobia [ 119 , 121 ].…”
Section: Osmophobiamentioning
confidence: 99%
“…Osmophobia has been proposed as a specific marker, helpful for the diagnosis of migraine [ 119 , 124 , 127 , 128 , 129 , 130 , 131 , 132 ]; however, it is not very sensitive [ 122 ]. Around half of the patients with migraines reported an increased sense of smell or reduced tolerability to smells [ 129 , 133 ].…”
Section: Osmophobiamentioning
confidence: 99%